2010
DOI: 10.1530/rep-09-0578
|View full text |Cite
|
Sign up to set email alerts
|

Development, embryonic genome activity and mitochondrial characteristics of bovine–pig inter-family nuclear transfer embryos

Abstract: The best results of inter-species somatic cell nuclear transfer (iSCNT) in mammals were obtained using closely related species that can hybridise naturally. However, in the last years, many reports describing blastocyst development following iSCNT between species with distant taxonomical relations (inter-classes, inter-order and inter-family) have been published. This indicates that embryonic genome activation (EGA) in xeno-cytoplasm is possible, albeit very rarely. Using a bovine-pig (inter-family) iSCNT mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 78 publications
4
24
1
Order By: Relevance
“…Control SPNT cow and sheep embryos as expected developed to the blastocyst stage; however, none of the cow-sheep or sheep-cow iSPNT embryos developed beyond the 8-to 16-cell stage, again the stage at which EGA occurs in both species. Taken together, our results support the argument that development of inter-species nuclear transfer embryos is highly inefficient with developmental arrest occurring at the stage of EGA specific to recipient cytoplast species (Chung et al 2009, Lagutina et al 2010. These recent reports have clearly demonstrated that the donor nucleus in iSCNT is only partially remodeled by the heterologous cytoplasm, and iSCNT embryos need to overcome nuclear-cytoplasmic compatibility issues before any further embryonic development to the blastocyst or later stages can be expected (Chung et al 2009, Lagutina et al 2010.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Control SPNT cow and sheep embryos as expected developed to the blastocyst stage; however, none of the cow-sheep or sheep-cow iSPNT embryos developed beyond the 8-to 16-cell stage, again the stage at which EGA occurs in both species. Taken together, our results support the argument that development of inter-species nuclear transfer embryos is highly inefficient with developmental arrest occurring at the stage of EGA specific to recipient cytoplast species (Chung et al 2009, Lagutina et al 2010. These recent reports have clearly demonstrated that the donor nucleus in iSCNT is only partially remodeled by the heterologous cytoplasm, and iSCNT embryos need to overcome nuclear-cytoplasmic compatibility issues before any further embryonic development to the blastocyst or later stages can be expected (Chung et al 2009, Lagutina et al 2010.…”
Section: Discussionsupporting
confidence: 88%
“…However, all intra-species SCNT embryos produced under the same conditions used for iSCNT developed to blastocyst stage. Our results were not different from several other recent reports (Chung et al 2009, Lagutina et al 2010, who had also reported that iSCNT embryos failed to reactivate the embryonic genome and arrested at the stage of EGA specific to the recipient oocyte. Conversely, inter-genus (Oh et al 2006, Yin et al 2006, inter-family (Dominko et al 1999, Zhao et al 2007, inter-order (Yang et al 2003, Wen et al 2005, Illmensee et al 2006, and even inter-class iSCNT (Chen et al 2002, Liu et al 2004 nuclear transfer embryos were reported to have Pig-mouse cytoplasmic hybrid embryos developed to the blastocyst stage.…”
Section: Discussioncontrasting
confidence: 69%
“…These embryos were characterized by prevailing nucleoplasmic nucleolin localization with occasional concentration around NPBs in some bovine and porcine nuclei. This pattern of nucleolin staining suggests the inability of these embryos to activate RNA polymerase I transcription and nucleoli formation and was identical to the pattern of nucleolin labeling in bovine and porcine SCNT embryos after inhibition of RNA polymerase I activity or EGA (Lagutina et al 2010). A similar pattern of nucleolin staining was found in all studied iSCNT embryos that did not form nucleoli in our experiments and was also shown for porcine-ovine (Hamilton et al 2004) and rhesus monkey-bovine (Song et al 2009) iSCNT embryos.…”
Section: Discussionsupporting
confidence: 86%
“…A similar pattern of nucleolin staining was found in all studied iSCNT embryos that did not form nucleoli in our experiments and was also shown for porcine-ovine (Hamilton et al 2004) and rhesus monkey-bovine (Song et al 2009) iSCNT embryos. The block of EGA in bovineporcine or porcine-bovine iSCNT embryos was confirmed by the absence of RNA polymerase II accumulation and its low activity, the absence of Nanog gene expression, a significantly lower level of mitochondrial mass in comparison with intra-species embryos, and a complete block of development at the 16-to 25-cell stage and 4-cell stage of iSCNT embryos, produced with bovine and porcine oocytes respectively (Lagutina et al 2010). Our data contradict previous reports (Dominko et al 1999, Uhm et al 2007) of 4-8% BL rates, implying at least partial xeno-genome activation in a wide set of iSCNT embryos.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation